Implementasi Nilai Kearifan Lokal Terhadap Pendidikan Karakter (Studi Kasus di MTs Pondok Tremas) - Machasinul Achlaq; Ahmad Yasin; Arif Kurniawan; Ahmad Holiq Amin (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Character education has become the main focus in overcoming the moral degradation that is rampant in Indonesian society. As mandated in the 1945 Constitution, Pancasila, and Law Number 20 of 2003. This article discusses the importance of character education as a core value of Indonesian education. The main focus is on the implementation of character education at MTs Pondok Tremas, taking into account the strong religious and traditional aspects in boarding school. The research method used is field research with a descriptive qualitative approach and data collection techniques through observation, interviews and documentation. Data was analyzed using data reduction, data display, and data verification. The research results show that character education at MTs Pondok Tremas is integrated into the school's vision and mission, by applying 18 character values in all aspects of learning and extracurricular activities. The approach used in forming student character includes seventeen character values, such as honesty, discipline, hard work, creativity and national spirit. Evaluation is carried out through direct assessment and observation of student attitudes. The role of teachers is very significant in developing character education, by utilizing classical methods and personal approaches. In conclusion, student character formation at MTs Pondok Tremas is carried out through a comprehensive approach which includes classroom learning, extracurricular activities and the role of the teacher. With good implementation, character education is expected to be able to produce a generation that has noble morals and strong character, ready to face future challenges.